Infrastructural temporalities: Facebook and the differential time of data management. Issue 1 (2nd January 2016) - Bollmer, Grant
Abstract : Facebook presents itself as a tool in the service of humanism: it connects people through the sharing of information and experience. This article contests these assumptions about the innate humanness of Facebook's connections through an examination of its information management and network architecture. It argues that Facebook depends on a number of radically different milieus expressed by way of different, competing conceptualizations of time that it does not or cannot negotiate. Consequentially, Facebook should not be imagined as a single network of human connectivity that will somehow realize newly identified human rights through technology. Facebook should be thought of as a multiplicity of incommensurate networks, not all of which can be brought into human experience. The time of infrastructure directs us to an uneven 'social' that emerges from the negotiation of multiple, often obscured forms of temporal difference, managed through multiple, often obscured systems of hardware and software that forever remain beyond the conscious experience of most Facebook users.